Investigation of the Relationship between Anthropometric Characteristics and Strength Values of Turkish Cadet Cyclists - Esra Kürkçü Akgönül; Ulaş Can Yıldırım (Sportif Bakış Spor ve Eğitim Bilimleri Dergisi, 2021)
In this study, it was aimed to examine the body composition, anthropometric and strength parameters of level cadet male cyclists at the national team level and to evaluate the relationship between the body composition, anthropometric and strength parameters. A total of 28 cadet male cyclists (age: 14.92±0.76, height:170,52±5.54, weight:60.47±5.59) participated in the study. Anthropometric characteristics of the subjects; height, body weight, body fat percentage, body mass index, skinfold thickness were measured, body fat percentage was determined using the “Yuhasz” formula, and motoric characteristics such as right and left handgrip strength, back strength and leg strength were measured. The analysis of the data was made in the SPSS statistical program and evaluated with the Pearson Correlation test. The result of the study, body fat percentage (8.949±1,104) and body mass index (20,786±1.555) were found. It was determined that the right handgrip strength (42,553±5,862), left handgrip strength (40.535±5,864), back strength (119,839±15,442) and leg strength (134,125±21,833) of the cadet cyclists were found. In addition, when the difference between handgrip strengths of the cyclists was examined, it was seen that the right hand was dominant. While there was a significant and positive correlation between body weight and right & left handgrip strength and back strength (r=0.478, p=0.01; r=0.405, p=0.032; r=0.409, p=0.031); it was determined that there was no correlation between body weight and leg strength (p>0.05). In addition, while there was an average significant and positive correlation was found between body mass index and only right handgrip strength (r=0.417, p=0.027), it was found that there was no significant correlation between age, height, fat ratio and strength parameters (p>0.05). As a result; this study showed that cadet cyclists have good hand grip, back and leg strength, and there is a significant correlation only between body weight and handgrip strength values, among the anthropometric characteristics. However, it was determined that there was no significant correlation between and anthropometric characteristics and leg strength, which is important for cyclists.